2020
DOI: 10.1007/s11739-020-02500-2
|View full text |Cite
|
Sign up to set email alerts
|

Neither ACEIs nor ARBs are associated with respiratory distress or mortality in COVID-19 results of a prospective study on a hospital-based cohort

Abstract: Considerable concern has emerged for the potential harm in the use of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor inhibitors (ARBs) in COVID-19 patients, given that ACEIs and ARBs may increase the expression of ACE2 receptors that represent the way for coronavirus 2 to entry into the cell and cause severe acute respiratory syndrome. Assess the effect of ACEI/ARBs on outcome in COVID-19 patients. Hospital-based prospective study. A total of 431 patients consecutively presenting at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 94%
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 94%
“…A total of 7087 potentially relevant articles were identified by our searching strategy. After excluding 6001 unqualified articles, 86 articles were involved in the subsequent analysis [2,4–7,9,10,14–16,20–95]. Of these, 23 studies contained multiple endpoints with two more kinds of comparisons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, since ACE2 is commonly targeted in antihypertensive treatment as well, it has been hypothesized that those patients may also have an increased risk for severe infection, due to an upregulated ACE2 expression caused by its inhibitors ( 43 ). However, antihypertensive treatment has not been associated with respiratory distress or mortality in hospitalized patients, but it remains unknown if it increases the risk for hospitalization ( 44 ).…”
Section: Introductionmentioning
confidence: 99%